Gender differences in heart transplantation: Twenty‐five year trends in the nationwide Spanish heart transplant registry. Issue 12 (14th October 2020) - García‐Cosío, María D.; González‐Vilchez, Francisco; López‐Vilella, Raquel; Barge‐Caballero, Eduardo; Gómez‐Bueno, Manuel; Martínez‐Selles, Manuel; Arizón, Jose M.; Rangel Sousa, Diego; González‐Costello, José; Mirabet, Sonia; Pérez‐Villa, Félix; Díaz‐Molina, Beatriz; et al.
Abstract: The study of gender differences may lead into improvement in patient care. We have aimed to identify the gender differences in heart transplantation (HT) of adult HT recipients in Spain and their evolution in a study covering the years 1993–2017 in which 6740 HT (20.6% in women) were performed. HT indication rate per million inhabitants was lower in women, remaining basically unchanged during the 25‐year study period. HT rate was higher in men, although this decreased over the 25‐year study period. Type of heart disease differed in men versus women ( p  < .001): ischemic heart disease 47.6% versus 22.5%, dilated cardiomyopathy 41.3% versus 34.6%, or other 36% versus 17.8%, respectively. Men were more frequently diabetics (18% vs. 13.1% p  < .001), hypertensives (33.1% vs. 24% p  < .001), and smokers (21.7% vs. 12.9% p  < .001), respectively. Women had more pre‐HT malignancies (7.1% vs. 2.8% p  < .001), and their clinical status was worse at HT due to renal function and mechanical ventilation. Adjusted survival ( p  = .198) and most of the mortality‐related variables were similar in men and women. Death occurred more frequently in women due to rejection (7.9% vs. 5.1% p  < .001) and primary failure (18.2% vs. 12.5% p  < .001) and in men due to malignancies (15.1% vs. 6.6% p  < .001).